Приключения Ульяны Караваевой - Варденбург Дарья (Лучшие книги детства, 2016)
Экземпляры: ф.9 (20191011) / Инвентарный номер: 59864 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: В 18 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-4